2011
DOI: 10.1002/kin.20608
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of elementary steps in the reaction of atomic bromine with 2,3‐dimethyl‐2‐butene under atmospheric conditions

Abstract: We have employed the laser flash photolysis-resonance fluorescence technique to investigate the gas-phase kinetics of elementary steps in the Br-initiated oxidation of 2,3-dimethyl-2-butene (TME) under atmospheric conditions. At T ≥ 274 K, measured rate coefficients are independent of pressure suggesting hydrogen abstraction as the dominant pathway. The following Arrhenius expression adequately describes all kinetic data at 274 K ≤ T ≤ 420 K: k 1a (T ) = (3.84 ± 0.84) × 10 −11 exp[(−169 ± 61)/T ] cm 3 molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…The database of experimental gas-phase rate constants k Br is less extensive and less internally consistent than those for k Cl or k OH , nor do we have the advantage of a compilation of evaluated and recommended values as we had for k Cl and k OH . In addition, because of the lower reactivity of Br•, Arrhenius parameters have typically been obtained at higher temperature and therefore require longer, and questionable, extrapolations to 298 K. A compilation is given in Table . All formulas have the carbon from which hydrogen abstraction occurs at the beginning followed by the substituents attached, that is, CH 3 X, CH 2 XY, or CHXYZ. For compounds with multiple potential abstraction sites, the experimental rate constant is typically assumed to be dominantly that of the most reactive site, a relatively safe assumption (see below) given the known high selectivity of Br•, compared with, for example, Cl•.…”
Section: Experimental Data Basementioning
confidence: 99%
See 3 more Smart Citations
“…The database of experimental gas-phase rate constants k Br is less extensive and less internally consistent than those for k Cl or k OH , nor do we have the advantage of a compilation of evaluated and recommended values as we had for k Cl and k OH . In addition, because of the lower reactivity of Br•, Arrhenius parameters have typically been obtained at higher temperature and therefore require longer, and questionable, extrapolations to 298 K. A compilation is given in Table . All formulas have the carbon from which hydrogen abstraction occurs at the beginning followed by the substituents attached, that is, CH 3 X, CH 2 XY, or CHXYZ. For compounds with multiple potential abstraction sites, the experimental rate constant is typically assumed to be dominantly that of the most reactive site, a relatively safe assumption (see below) given the known high selectivity of Br•, compared with, for example, Cl•.…”
Section: Experimental Data Basementioning
confidence: 99%
“…More recent methods have followed the decay of Br• in real time in an excess of RH by resonance fluorescence spectroscopy or mass spectrometry after its generation by a short flash photolysis or discharge pulse. This approach has been applied to ethane, neopentane, propylene, E -2-butene, 2,3-dimethyl-2-butene, , methanol, dimethyl sulfide, dimethyl sulfoxide, propane, n -butane, bromochloromethane, and i -butane. ,, …”
Section: Experimental Data Basementioning
confidence: 99%
See 2 more Smart Citations
“…Acrolein and formaldehyde have been noticed as the initial products from those reactions and considerably furan from the reaction with OH, and nitrates from the reaction with NO 3 [5,11]. There were some studies suggested that a possible reaction of 2,3-dimethyl 2butene with bromine may be participated in elimination of this compound from the atmosphere [13].…”
Section: Introductionmentioning
confidence: 99%